(untitled) (Journal of Oriental Studies, 2016)
A social portrait has become widely used in research and in recent years is already beyond the sociology. Compilation of sociological (or social) portrait became necessary not only in the theoretical aspect, but also in practical. The main methods are questionnaires, interviews, online surveys, etc. A carefully compiled social portrait enables briefly describe one or another group of people school or higher education, medicine, religion, nation, state. On the basis of the methodological foundations of drawing portraits and study different methods of a core of a variety of characteristics that describe the material, cultural, gender, demographic situation of portrayed people.